2020
DOI: 10.1111/add.14899
|View full text |Cite
|
Sign up to set email alerts
|

Zoned in or zoned out? Investigating immersion in slot machine gambling using mobile eye‐tracking

Abstract: Background and Aims Immersion during slot machine gambling has been linked to disordered gambling. Current conceptualizations of immersion (namely dissociation, flow and the machine zone) make contrasting predictions as to whether gamblers are captivated by the game per se ('zoned in') or motivated by the escape that immersion provides ('zoned out'). We examined whether selected eye-movement metrics can distinguish between these predictions. Design and Setting Pre-registered, correlational analysis in a labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Instead, when the attachments of OGVs start to act as a ‘fluid’ or a ‘bush fire’, they become mediators of othering and juxtapose the actor networks of ‘normal life’ with gambling ( Law, 2011 ). In the ensuing struggle, the gambling-related assemblages first circulate a zone ( Murch et al., 2019 ; Schüll, 2012 ) that provides momentary escape, trance or excitement away from the hardships of everyday life. When the difficulties become too big to overcome, they lose their ability to convey this relief, and are translated to distribute the opposite emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, when the attachments of OGVs start to act as a ‘fluid’ or a ‘bush fire’, they become mediators of othering and juxtapose the actor networks of ‘normal life’ with gambling ( Law, 2011 ). In the ensuing struggle, the gambling-related assemblages first circulate a zone ( Murch et al., 2019 ; Schüll, 2012 ) that provides momentary escape, trance or excitement away from the hardships of everyday life. When the difficulties become too big to overcome, they lose their ability to convey this relief, and are translated to distribute the opposite emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Murch et al . demonstrated that specific patterns of eye movements (i.e. percentage of eye fixation on the game's credit window) offer a relevant marker of gambling‐related immersion experience among a sample of slot‐machine gamblers.…”
mentioning
confidence: 99%
“…The present commentary proposes that research on gambling disorders capitalize on the findings from Murch et al . to progress towards a fine‐grained understanding of an increasingly popular gambling habit, namely sports betting. Through easy access from a computer, tablet or telephone it is now possible to gamble on any sports event at any moment, such as before or during a game in play, and while being exposed to a high number of sports betting advertisements .…”
mentioning
confidence: 99%
See 2 more Smart Citations